(untitled) - Mantchev, Lisa; Yoo, Taeeun (New York, 2015)
A boy is excluded from joining his friends' pet club because of his unusual pet.
Keywords: Elephants as pets; Juvenile fiction; Pets; Juvenile fiction; Toleration; Juvenile fiction; Elephants as pets; Fiction; Pets; Fiction; Toleration; Fiction